DYNAMICS O EQUINE SKIN TEMPERATURE DURING PHYSICAL ACTIVITY BY INFRARED TERMOGRAPHY - de Oliveira, K.; Oliveira, G. A. C.; da Silva, D. A.; Bueno, L. G. F.; Lopes, A. M.; de Moura, D. J. (Revista Brasileira de Engenharia de Biossistemas, 2018)
The objective was to describe the changes in the skin temperature of horses during exercise obtained through infrared thermography, as well as to evaluate the functioning of muscle groups in response to physical activity. Ten equine Quarter Horse athletes were used, delineated in subdivided plots, resulting in ten replicates per treatment. The treatments consisted of thermographic evaluations of skin temperature (St) of resting moment (RM)) and at two moments during exercise, 5 (M5) and 10 min (M10), totaling in three treatments. The obtained thermograms were analyzed for the specific and general region of the horse’s body. The specific regions resulting in five muscular regions representing the neck, thoracic limb, dorsum, abdomen and pelvic limb. There was no significant effect (P> 0.05) of the exercise on the St of the body areas located in the neck, thoracic limb and back. Evaluations performed with 5 min of physical activity, compared to RM, resulted in superior Tp (P <0.05) for the abdominal region. The Tp monitored with 10 min of exercise compared to RM showed an increase (P <0.05), only for the abdominal and pelvic region. It was concluded that the use of infrared thermography allows to accurately identify changes in the skin temperature of resting and exercised horses. The abdominal and pelvic muscles were the main muscle groups activated during physical activity in horses.